De Viena a Wiesbaden: O percurso do pensamento clínico-teórico de Sándor Ferenczi - Gomes, Gustavo Dean (2016)
The purpose of this study is to present the development of the theoretical and clinical thinking of Sándor Ferenczi, a Hungarian psychoanalyst who lived between 1873 and 1933. This research started as an attempt to understand the problems and the possible ways to handle psychical illnesses which this author found along his practice. The fact that Ferenczi’s theories were unconventional contributed to his work being neglected for a long period. However, it has recently been revitalized as an important reference to the ethics of care in psychoanalysis. We will examine the several phases of the author’s production, from his graduation as a doctor in Vienna to his meeting Sigmund Freud and learning of his psychoanalytical theory, covering his experience as a neurologist in Budapest. From then, we will have the opportunity to observe his contributions to establishing psychoanalysis classical technique in the 1910s, as well as the innovations he proposed in clinical interventions starting in the 1920s: the active technique, the elasticity of the psychoanalytic technique, the relaxation principle and the mutual analysis. We will simultaneously study his most relevant theoretical conceptions to understand how they were intertwined and how they supported his characteristic clinical style, as well as the personal and theoretical relationship he maintained with the pioneers of the psychoanalytical method (Freud, Otto Rank, and Georg Groddeck, among others)